The power of imagination In The Red Shoes - Kamila Drapało (Studia z Teorii Wychowania)
In the 1948 movie The Red Shoes, the power of imagination and artistic vocation are metaphorically represented as a pair of red dancing shoes. Just as in Andersen’s fable, the shoes are enchanted: they can open up new horizons and possibilities of existence and artistic expression to the one that wears them. But their inexhaustible power can also possess her, demand complete devotion, or even dance her to death. A hermeneutic reading of the three key scenes from the movie inspires a reflection on the dialectics of the power of imagination and its productive as well as destructive potential.